GAMBARAN PENGETAHUAN DAN SIKAP SISWA TENTANG KESIAPSIAGAAN MENGHADAPI GEMPA BUMI DI SMAN 3 PAINAN TAHUN 2022 - Zeswita, Armein Lusi; Indriati, Gustina; Sitepu, Nurlaila (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
West Sumatra is an area that often experiences earthquakes and one of them is the South Coast which often experiences earthquakes and West Sumatra is a red zone which is prone to earthquakes. Children are part of a community that is vulnerable to earthquake hazards. The large number of losses and victims is caused by a lack of awareness and knowledge about disasters, both the vulnerability of the area of residence and the lack of knowledge about rescue actions when a disaster occurs. This study aims to determine the knowledge and attitudes of SMAN 3 Painan students regarding earthquake preparedness. SMAN 3 Painan is 700 meters from the beach and this school is a boarding school for students. The design of this research is descriptive quantitative, and conduct research at SMAN 3 Painan in 2022. The number of students is 219 people and the respondents for the research are SMAN 3 Painan students, totaling 141 people and the sampling technique is using random sampling. The research measuring tool is using a questionnaire and data analysis with univariate analysis. Based on the results of the study it was found that students who had good knowledge were 101 people (71.6%) and had sufficient knowledge as many as 24 people (17%) and 16 people (11.3%) had less knowledge. For the assessment of student attitudes, it was found that 49 students (34.8%) had sufficient attitudes. It is suggested to the school related to earthquake preparedness and find out about evacuation routes and know the assembly points in the event of an earthquake.